PENGEMBANGAN MEDIA BOOKLET SCIENCE FOR KIDS SEBAGAI SUMBER BELAJAR DI SEKOLAH DASAR - Tiurida Intika (JRPD (Jurnal Riset Pendidikan Dasar), 2018)
Media booklet dapat dijadikan sumber belajar karena bentuknya sederhana serta menyediakan data akurat yang dapat membantu siswa memahami konsep materi. Tujuan pengembangan adalah untuk mengetahui pentingnya cara pengembangan serta efektivitasnya. Penelitian ini merupakan penelitian Research and Development (RD) yang dilakukan mengacu pada teori Borg dan Gall. Data yang diambil adalah kebutuhan pengembangan booklet, kelayakan booklet, tanggapan siswa mengenai kelayakan booklet dan hasil belajar siswa melalui media booklet. Hasil penelitian menunjukkan bahwa guru dan siswa memberikan tanggapan positif terhadap penggunaan booklet. Terlihat pada penilaian validasi produk booklet dari pakar materi dan media yang memperoleh skor rata-rata 3,28 dengan kriteria sangat baik atau layak digunakan. Siswa memberikan tanggapan dan respon positif sangat baik dengan memperoleh skor rata-rata sebesar 9,26%. Sedangkan ketuntasan hasil belajar siswa dengan ≥75 pada uji coba pemakaian 84,5%. Berdasarkan hasil penelitian dapat disimpulkan bahwa media booklet science for kids booklet efektif dan layak digunakan untuk meningkatkan hasil belajar siswa dan dikembangkan berdasarakan kebutuhan guru dan siswa.  Media booklet can be used as a source of learning because it is simple and provides accurate data that can help students understand the concept of the material. The purpose of development is to know the importance of development and its effectiveness. This research is a Research and Development (R D) research which is done referring to Borg and Gall theory. The data taken is the need of booklet development, booklet feasibility, student responses about booklet feasibility and student learning outcomes through booklet media. The results showed that teachers and students responded positively to the use of booklets. Seen on the validation assessment of product booklets from material and media experts who scored an average of 3.28 with criteria very good or feasible to use. Students responded positively very well with an average score of 9.26%. While the completeness of student learning outcomes with ≥75 on the trial use 84.5%. Based on the results of the study can be concluded that the media booklet science for kids booklet effective and worthy used to improve student learning outcomes and developed based on the needs of teachers and students. Media booklet can be used as a source of learning because it is simple and provides accurate data that can help students understand the concept of the material. The purpose of development is to know the importance of development and its effectiveness. This research is a Research and Development (R D) research which is done referring to Borg and Gall theory. The data taken is the need of booklet development, booklet feasibility, student responses about booklet feasibility and student learning outcomes through booklet media. The results showed that teachers and students responded positively to the use of booklets. Seen on the validation assessment of product booklets from material and media experts who scored an average of 3.28 with criteria very good or feasible to use. Students responded positively very well with an average score of 9.26%. While the completeness of student learning outcomes with ≥75 on the trial use 84.5%. Based on the results of the study can be concluded that the media booklet science for kids booklet effective and worthy used to improve student learning outcomes and developed based on the needs of teachers and students.